Risk Management For All Levels Of Business, Underestimated Perspective - Soetam Rizky Wicaksono; Abdul Hakim (Universitas Muhammadiyah Ponorogo, 2023)
Risk analysis is needed in enterprises and various fields, including military, information technology, financial institutions and investments . So proper learning about risk is needed in various fields, both by implementers and decision makers. Although the risk is a probability science that may occur and may not occur, the uncertainty must still go through an appropriate assessment so that it can be a preparation for all parties involved in the activity. Therefore, a book on risk management was chosen in this review that specifically discusses risk management in medium and small companies. Because not many books discuss risk management in that scope specifically, it is worth discussing to open the insights of small and medium entrepreneurs, as well as academics, that risk management in that scope also needs to be studied in depth. In addition, given that the publisher of this book is the leading publisher (Routledge) in the field of academic books, there is no doubt about the book's quality in general. Therefore, it is hoped that the results of this book review can pave the way for academics and practitioners to further explore and find more about risk management references in the scope of small and medium enterprises.